Dl-3-n-Butylphthalide Alleviates Demyelination and Improves Cognitive Function by Promoting Mitochondrial Dynamics in White Matter Lesions - Feng, Yiwei; Guo, Min; Zhao, Hongchen; Han, Sida; Hao, Yining; Yuan, Yiwen; Shen, Weiwei; Sun, Jian; Dong, Qiang; Cui, Mei (Frontiers in Aging Neuroscience, 2021)
White matter lesions (WML) is a type of cerebral vascular disorder accompanied by demyelination and cognitive decline. Dl-3-n-butylphthalide (DI-NBP) is a neuroprotective drug used for the treatment of ischemic cerebrovascular diseases while the function of DI-NBP on WML is still not clear. This study aims to investigate whether DI-NBP affects cognitive function and ameliorates demyelination in a model of WML. The BCAS mouse model and in vitro brain slides culture with low glucose and low oxygen treatment were adopted. Dl-NBP were administered intragastrically for 28 days after BCAS or added at the dose of 50 μM for 48 h after LGLO. Spatial learning and memory were evaluated by eight-arm radial maze. The demyelination was detected using TEM. Mitochondria dynamics was assessed by time-lapse imaging in cultured brain slices. The function of the synapse was evaluated by patch clamp. In BCAS mice, obvious demyelination and cognitive decline were observed, while both were significantly relieved by a high-dose DI-NBP treatment (100mg/kg). Along with the demyelination, the mitochondria accumulation in axons was significantly increased in BCAS mice, but with the treatment of a high-dose DI-NBP, mitochondria accumulation mitigated, and the anterograde/retrograde transport of mitochondria was increased. Following the improved anterograde/retrograde transport of mitochondria, the synapse activity was significantly upregulated while the ROS generation was remarkably decreased in the cultured brain slices. In addition, we identified syntaphilin (SNPH) as the downstream target of DI-NBP. The overexpression of SNPH mediated the effects of DI-NBP in mitigating axonal mitochondria accumulation. In conclusion, DI-NBP treatment significantly relieved demyelination, improved spatial learning and memory in the WML model through promoting mitochondria dynamics. These neuroprotective effects of DI-NBP were mediated by inhibiting mitochondria arching protein SNPH, which provided a potential therapeutic target for WML.